Postprandial glycemic response to isocaloric protein load in men with different types of fat distribution - M. Yu. Sorokin; B. B. Pinkhasov; V. G. Selyatitskaya (Сибирский научный медицинский журнал, 2024)
Aim of the study was to quantify postprandial glucose levels in response to isocaloric protein load at main meals in men with different types of fat distribution. Material and methods. The study enrolled men aged 25 to 65 years. Group 1 (n = 17) consisted of obese men with subcutaneous fat distribution (SFD) type while group 2 (n = 16) was represented by obese men with abdominal type of fat distribution (AFD). Group 3 (comparators) consisted of 10 men with normal body weight (NBW). Glycemic response to standard isocaloric protein load was assessed by the results of glucose levels within 3 hours starting 5 minutes after end of food consumption on different days and mealtime. Standard protein lunch was introduced during the second day while standard protein dinner and breakfast were performed at the third and fourth days respectively. Results. It was found that protein intake leads to neither pronounced postprandial glycemic fluctuations nor decrease in glucose levels by the end of the 3rd hour of the test. Accordingly, it also doesn’t provoke hunger, unlike carbohydrate intake does. In men with NBW a more pronounced increase in glucose level after protein meal was found, both relative to the baseline levels and comparing with men from SFD and AFD groups. In NBW group at lunchtime and especially in the evening a double-humped glycemic curve was noted. Glycemic variability in men with different types of fat distribution was characterized by the fact that glycemic increment was more pronounced in men with AFD than in men with SFD whose glycemic curve was almost flat after all meals. Conclusions. Protein intake in men with NBW and different types of fat distribution does not lead to significant changes in postprandial glucose levels. Glycemic fluctuations don’t exceed 1 mmol/L within a 3-hour period after consuming of isocaloric breakfast, lunch or dinner. Protein intake results in greater postprandial glucose levels in men with AFD than in SFD men.